Pelaksanaan Dana Desa Di Desa Karangsalam Kidul KecamatanKedungbanteng Kabupaten Banyumas - Estiningrum; Ninik Hartariningsih (Wijayakusuma Law Review, 2020)
In order to improve services and community welfare, villages have the right to obtain Village Funds from theCentral Government sourced from the State Revenue and Expenditure Budget (APBN). The condition ofKarangsalam Kidul Village before receiving the Village Fund was seen in terms of facilities and infrastructure suchas roads, bridges and schools which were still inadequate. Infrastructure development is hampered by limited fundsowned by the village government. Under these conditions, it is difficult for Karangsalam Kidul Village to budget fordevelopment even though this is deemed important as supporting the life of the village community. The existence ofthe Village Fund in Karangsalam Kidul Village shows the benefits of the Village Fund for the local villagecommunity. Various Village developments have been carried out by Karangsalam Kidul Village since obtainingVillage Funds from the Government. Based on the results of the interviews, the people of Karangsalam Kidul Villagefelt that there was a change both in terms of the economy, village facilities and infrastructure as well as from thesocial side.